Optimization of Performance Management of the Bogor Regency General Election Commission Ahead of the 2024 Election: Realizing Clean and Good Governance - Nascar Aliefa Dhafaz; Musnaini; Hendriyaldi (Journal of Humanities, Community Service, and Empowerment, 2025)
This study aims to explore the steps taken by the Bogor Regency General Election Commission (KPU) in preparing for the 2024 Election by implementing the principles of Clean and Good Governance (CGG). The primary focus of this study is to analyze how the Bogor Regency KPU manages the election process, ensuring transparency, accountability, and participation at every stage of the election. Based on the results of in-depth interviews with the Head of the Bogor Regency KPU, KPU members, and election supervisors, this study found that the Bogor Regency KPU has made efforts to strengthen its organizational structure and increase human resource capacity through systematic training, to ensure that the implementation of the 2024 Election runs smoothly and without any potential irregularities. Despite various challenges, such as a lack of human resources (HR) and delays from political parties in submitting prospective DPRD candidates, the Bogor Regency KPU continues to strive to optimize performance through the application of information technology and strict supervision. The use of technology and social media, such as Instagram, to increase transparency and facilitate public participation in elections is an integral part of the Bogor Regency KPU's efforts. It is hoped that, with the consistent application of the CGG principle, the 2024 Election in Bogor Regency will run smoothly and produce legitimate leaders, thereby increasing public trust in a more democratic election system.